WORKSHOP PENGELOLAAN PEMBELAJARAN JARAK JAUH BERBASIS APLIKASI VIDEO CONFERENCE - Hanim Faizah; Susilohadi; Lydia Lia Prayitno; Erlin Ladyawati; Ninik Mutianingsih (STKIP PGRI Sidoarjo, 2021)
Schools that carry out online learning should be accustomed to following the development of Multimedia technology. However, this does not necessarily apply to all schools that carry out learning through online media. From the results of direct interviews with teachers and deputy principals, that teachers still have difficulty in using multimedia for the learning process, even though online learning, especially the use of video conferencing is a must in the current pandemic era. For this reason, this Community Service Program is deemed necessary to be implemented at SMKN 1 Jetis, Mojokerto. To overcome this problem, a distance learning management workshop based on video conference applications will be held, which will be carried out in 5 stages, namely the introduction of the Zoom Meeting application, a workshop on the implementation of learning using the Zoom Meeting application, the introduction of the Google Meet application, a workshop on the implementation of learning using the Google Meet application, and review the implementation of the workshop. As a result of these activities, teachers at SMKN 1 Jetis, Mojokerto better understand the use of video conferencing applications in depth to carry out video conference-based distance learning. However, in the implementation there are still shortcomings such as unstable internet signal, unclear display, and the training arena that must be carried out separately from one group to another causing the committee to be less than optimal in controlling the implementation.